Conventional Domestic Waste Management Using Environmentally Friendly Compositing Technology in Indonesia: A Review - Apriliyah April; Tatya Devina Pratiwi; La Ode A. Muh. Afif Rizqullah (Journal of Epidemiology and Health Science, 2026)
Background: Domestic waste has become an increasingly significant environmental challenge due to population growth, urbanization, and changing consumption patterns. The increasing volume of household waste places substantial pressure on waste management systems and contributes to environmental degradation, public health risks, and social problems. Limited infrastructure and low public awareness further hinder effective waste management, making the adoption of environmentally friendly technologies essential for sustainable development. Objectives: This study aims to review technological innovations and approaches in domestic waste management and evaluate their effectiveness in reducing waste generation and supporting environmental sustainability. Methods: A literature review was conducted using 20 relevant scientific articles retrieved from the Google Scholar database. The selected studies were analyzed to identify current trends, challenges, and opportunities in domestic waste management technologies. Results: The findings indicate that various technologies, including composting, eco-enzymes, bioplastics derived from agricultural waste, liquid organic fertilizers, and automated composting systems, effectively reduce waste volume, produce value-added products, and enhance environmental awareness. However, the implementation of these technologies is constrained by low community participation, inadequate facilities, and limited policy support. Conclusion: Technology-based domestic waste management offers considerable potential to improve environmental sustainability and reduce waste-related impacts. Its successful implementation requires strong stakeholder collaboration, supportive policies, community engagement, and continuous innovation to achieve an effective and sustainable waste management system. Keywords: domestic waste, waste management, eco-friendly technology, composting, sustainable development.